(untitled) (L’architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2015)
Sir Edwin Lutyens (1869-1944) was one of the most inventive and prolific Classical architects in Britain in the twentieth century, and his work is now much admired around the world. To understand his mature buildings, how they were conceived, detailed and executed, one needs to understand the man, and the story of his evolution as an architect. This paper explains that journey. From his unusual education in his youth, and the Arts and Crafts Movement into which as a young architect he was born; his early integration of Classical details within vernacular designs; his ‘Wrenaissance’ (increasing fascination with the work of Sir Christopher Wren [1632-1723]) and his evolution into full blown canonical Classical designs, and then the final flowering into abstract Classicism and the style that he was to make his own.